Laryngeal cancer in Finland: A 5‐year follow‐up study of 366 patients. Issue 1 (27th January 2015) - Haapaniemi, Aaro; Koivunen, Petri; Saarilahti, Kauko; Kinnunen, Ilpo; Laranne, Jussi; Aaltonen, Leena‐Maija; Närkiö, Mervi; Lindholm, Paula; Grénman, Reidar; Mäkitie, Antti; Atula, Timo; ,
ABSTRACT: Background: The purpose of this study was to acquire nationwide data on the management and outcome of laryngeal squamous cell carcinoma (SCC) in Finnish university hospitals over a 5‐year posttreatment follow‐up. Methods: All records of patients diagnosed and treated for primary laryngeal SCC during 2001 to 2005 were reviewed. Results: Three hundred sixty‐six patients with laryngeal cancer were identified, 360 of whom had laryngeal SCC. Three hundred forty‐two patients with laryngeal SCC (95%) were treated with curative intent. Five‐year disease‐specific survival (DSS) for T1a, T1b, T2, T3, and T4 glottic SCC was 100%, 95%, 78%, 79%, and 53%, respectively. The corresponding figures for T1 to T4 supraglottic SCC were 68%, 54%, 72%, and 59%. Conclusion: Results of this nationwide study give a general overview of the outcome of unselected patients treated with unified guidelines. Patients with T2 tumors, usually treated with radiotherapy (RT), had a worse prognosis than expected. This patient group warrants further investigation and possibly treatment intensification. © 2015 Wiley Periodicals, Inc. Head Neck 38: 36–43, 2016